PENDAMPINGAN PENYUSUNAN INSTRUMEN EVALUASI PEMBELAJARAN PADA GURU PJOK DI KABUPATEN MALUKU TENGGARA - Rumahlewang, Emma; Solissa, Jonas; Hasbullah, Bahmid; Hatu, Mesak; Syaranamual, Jusak (German für Gesellschaft (J-Gefüge), 2025)
The purpose of this community service activity is to improve teachers' competence in designing and developing effective learning evaluation instruments, which in turn is expected to improve the quality of student learning outcomes in PJOK learning. The method used in this service is the Technical Assistance Model in the form of training. The partners in this service are elementary school PJOK teachers in Maluku Tengara Regency, totaling 18 people. The instruments used to measure the achievement of the training activities were pre-tests and post-tests. The test results were then analyzed descriptively. The results of this training and mentoring showed an increase of 18% and were in the “moderate” category.